Fruits and Vegetables Consumption Relationship with Hypertension in the Elderly Villager of Bolon, Colomadu Karanganyar - Prakosa, Muhammad Ardianto; ., Bagus Wicaksono; Damayanti, Kusmadewi Eka (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Backgrounds: Fruits and vegetables intake was associated with lower risk of hypertension especially to elderly which have more complication disease. There was evidence that a diet rich in fruit and vegetables reduces blood pressure (sistolic and diastolic). This observation aimed to examine whether fruits and vegetables intake between elderly villagers was related to hypertension. Methods: This study was an observational study with a cross-sectional approach in the elderly villager of Bolon, Colomadu, Karanganyar. Subjek was 72 elderly aged â¥ 60 years. Baseline intake of fruits and vegetables was assessed by food frequency questionnaires. Fruits and vegetables group was divided into banana, apple, spinach, and tomato which was in journal can reduced blood pressure (sistolic and diastolic). Chi-square test was used to examine relationship fruit and vegetable consumption with hypertension. Results: Chi-square test frequency of consumption banana, apple, spinach and tomato with hypertension consecutive p-value = 0.681, 0.320, 0.122, 0.315. Conclusions: There was no relationship frequency of consumption of bananas, apples, spinach, and tomatoes with hypertension. Keywords: hypertension, fruit consumption, vegetable consumption, elderly